TAFSIR QUR’AN SURAH AL-BAQARAH: 30-31 DALAM PERSPEKTIF PENDIDIKAN KONTEMPORER - Arif Zefrizen; Dwi Ratnasari; Hidar Amaruddin (Raudhah - Proud To Be Professional, 2024)
Abstract Education is a conscious and planned effort to form human potential. This research aims to determine the educational values ​​contained in Surah Al - Baqarah verses 30 - 31. This research uses a qualitative approach with the type of library research. The analysis technique used is content analysis. The educational values ​​contained in QS. Surah Al-Baqarah verses 30 – 31, namely First, the obligation to ask people who do not know to those who know better. and you should not rebuke the person who asks, but it is better if the question is answered or transferred to another gently. Second, it shows the glory of science and the superiority of knowledgeable people over wicked people and the superiority of people who admit their incompetence and shortcomings. So the knowledge bestowed by Allah SWT in the form of knowledge provides teaching meaning so that humans always obey and comply with His commands. Keywords: Tafsir, QS. Al -Baqarah ayat 30 – 31, Education Values